The influence of different turbulence models on the diffusion coefficients of energetic particles. Issue 6 (12th June 2015) - Hussein, M.; Tautz, R. C.; Shalchi, A.
Abstract: We explore the influence of turbulence on the transport of energetic particles by using test particle simulations. We compute parallel and perpendicular diffusion coefficients for two‐component turbulence, isotropic turbulence, a model based on Goldreich‐Sridhar scaling, noisy reduced magnetohydrodynamic turbulence, and a noisy slab model. We show that diffusion coefficients have a similar rigidity dependence regardless which turbulence model is used, and thus, we conclude that the influence of turbulence on particle transport is not as strong as originally thought. Only fundamental quantities such as particle rigidity and the Kubo number are relevant. In the current paper we also confirm the unified nonlinear transport theory for noisy slab turbulence. To double check the validity and accuracy of our numerical results, we use a second test particle code. We show that both codes provide very similar results confirming the validity of our conclusions. Key Point: We study the influence of turbulence on the transport of energetic particles